On The Theory Of Diophantine Approximations And Continued Fractions Expansion. - Haili, Hailiza Kamarul; Rosli, Norhayati (2005)
Approximation of irrational numbers by the rationals has been studied for decades and one of the methods to approximate the irrationals is by using the diophantine approximation and the convergents of its continued fractions expansion.